Sleep Time and Depression Symptoms as Predictors of Cognitive Development Among Adolescents: A Cross-Lagged Study From China - Cao, Xiaojie (Psychological reports, 2025)
Sleep time and depression symptoms are important factors affecting cognitive development in adolescents. Based on the China Education Panel Survey (CEPS) database, this study used a two-wave cross-lagged model to examine the bidirectional relationship between sleep time, depression symptoms, and cognitive development. Descriptive statistics showed that Chinese adolescents' cognitive development increased significantly from 7th to 8th grade in junior high school, but unfortunately, their depression level and average sleep time per night demonstrated a slightly deteriorating trend. Correlation analysis showed that there was a relatively stable negative correlation between cognitive development, sleep time, and depression symptoms. Moreover, the cross-lagged model revealed that there was a bidirectional relationship between cognitive development and sleep time, a bidirectional relationship between depression symptoms and sleep time, and a unidirectional relationship between depression symptoms and cognitive development. Male adolescents in the subgroup were consistent with the total sample. Among female adolescents, only cognitive development and sleep time have a bidirectional relationship, while depression symptoms and cognitive development, and depression symptoms and sleep time have a unidirectional relationship. Therefore, it is of significance to take targeted action to promote cognitive development and healthy growth in adolescents worldwide.